Discovery based high resolution MS/MS analysis for selection of allergen markers in chocolate and broth powder matrices. (1st May 2021) - Pilolli, Rosa; Van Poucke, Christof; De Angelis, Elisabetta; Nitride, Chiara; de Loose, Marc; Gillard, Nathalie; Huet, Anne-Catherine; Tranquet, Olivier; Larré, Colette; Adel-Patient, Karine; Bernard, Hervé; Mills, E.N. Clare; et al.
Highlights: Chocolate and broth powder were incurred with six allergenic ingredients (milk, egg, peanut, soybean, hazelnut, and almond). Discovery analyses were carried out by HR-MS/MS analysis on both incurred matrices. Different conditions for sample preparation were tested and a single best protocol was identified. A list of potential markers for all ingredients was collected in both matrices with some shared options. DIA analysis allowed identifying a preliminary set of reliable transitions according to their sensitivity. Abstract: Peptide marker identification is an important step in development of a mass spectrometry method for multiple allergen detection, since specificity, robustness and sensitivity of the overall analytical method will depend on the reliability of the proteotypic peptides. As part of the development of a multi-analyte reference method, discovery analysis of two incurred food matrices has been undertaken to select the most reliable peptide markers. Six allergenic ingredients (milk, egg, peanut, soybean, hazelnut, and almond) were incurred into either chocolate or broth powder matrix. Different conditions of protein extraction and purification were tested and the tryptic peptide pools were analysed by untargeted high resolution tandem mass spectrometry and the resulting fragmentation spectra were processed via a commercial software for sequence identification. The analysis performed on incurred foods provides both a prototype effective and straightforward sample preparation protocol and delivers reliable peptides to be included in a standardized selected reaction monitoring method.